Acute fatigue effects on ground reaction force of lower limbs during countermovement jumps - Carlos Gabriel Fábrica; Paula V. González; Jefferson Fagundes Loss (Universidade Estadual Paulista (UNESP), 2013)
Parameters associated with the performance of countermovement jumps were identified from vertical ground reaction force recordings during fatigue and resting conditions. Fourteen variables were defined, dividing the vertical ground reaction force into negative and positive external working times and times in which the vertical ground reaction force values were lower and higher than the participant's body weight. We attempted to explain parameter variations by considering the relationship between the set of contractile and elastic components of the lower limbs. We determined that jumping performance is based on impulsion optimization and not on instantaneous ground reaction force value: the time in which the ground reaction force was lower than the body weight, and negative external work time was lower under fatigue. The results suggest that, during fatigue, there is less contribution from elastic energy and from overall active state. However, the participation of contractile elements could partially compensate for the worsening of jumping performance.